The Sociological Imagination of Meals on Wheels: How a Home Delivered Meal Program Sheds Light onto Larger Social Issues. - Zachary Hozid; David Fazzino (Social Work and Society)
Service organizations provide a multitude of services beyond their stated goals. They serve not only specific clients with specific measurable deliverables, but in a more holistic sense they alsooffer accessory products in the exchange of goods and services including fostering human relationships between providers and those receiving the goods and services.These service organizations and the relationships they foster are mediated by historical and contemporary social, economic, and political structures.Drawing from three years of field-based experiences, surveys, and interviews, this paper employs C. Wright Mills (1959) Sociological Imagination to holistically consider these relationships. From the specific case-study analysis of Juneau, Alaska's Meals on Wheels program, it argues for a more holistic analysis in order to improve service delivery.